Characteristics and Course Recommendations of Agricultural Communicators: An Update - Eugene Kroupa; James Evans (Journal of Applied Communications, 1976)
Our recent national survey of agricultural communicators was designed to reveal more about these professionals and obtain their academic course recommendations and other suggestions for college students preparing for similar careers.